Influence of impaired glucose tolerance and type 2 diabetes on the multimorbidity cluster of cardiovascular disease and cancer: a post hoc analysis of the Da Qing Diabetes Prevention Outcome Study - Fei Chen; Jinping Wang; Siyao He; Yifan He; Yali An; Qiuhong Gong; Xiaoping Chen; Ying Shuai; Xuan Wang; Yanyan Chen; Bo Zhang; Guangwei Li (BMC Medicine)
Abstract Background This study explored the influence of type 2 diabetes and impaired glucose tolerance (IGT) on the risk of the multimorbidity cluster of cardiovascular disease (CVD) and cancer. Methods A total of 1629 participants in the Da Qing Diabetes Prevention Outcome Study were recruited in the present analysis, including normal glucose tolerance (NGT, N = 492), IGT (N = 540), and newly diagnosed type 2 diabetes (N = 597) groups. Cox proportional hazards analyses were performed to assess the relationship between NGT, IGT, and newly diagnosed type 2 diabetes and the risk of the multimorbidity cluster of CVD and cancer. Results The incidence rates for multimorbidity cluster CVD and cancer were 1.25, 3.17, and 3.23 per 1000 person-years in people with NGT, IGT, and the newly diagnosed type 2 diabetes groups, respectively, over 34-year follow-up. Cox analysis revealed that diabetes status (as time-dependent variable) was significantly associated with the subsequent increased risk of multimorbidity cluster of CVD and cancer compared with non-diabetes (hazard ratios [HR] = 2.55, 95% confidence interval [CI] 1.51–4.31) after adjustment of potential confounders. Similar analysis showed that this risk was significantly higher in the IGT and newly diagnosed type 2 diabetes groups compared with NGT, with HR of 3.28 (95% CI 1.83–5.87) and HR of 3.90 (95% CI 2.14–7.09), respectively. Whereas compared diabetes with IGT group, this risk was not significantly different. Conclusions Similar to newly diagnosed type 2 diabetes, IGT is significantly associated with an increased risk of the multimorbidity cluster of CVD and cancer compared with NGT. This finding highlights the urgent need for an active detection of IGT and effective prevention and management of diabetes.